Pressure, Time, and Type of Gas of Micro-Nanobubbles on the Removal of Heavy Metals - As, Sb, and Cd in Acidic Effluents - Juan Antonio Vega Gonzalez; Aldo Roger Castillo Chung; Luis Anthony Rojas Sisniegas; Luis Wilfredo Aguilar Rodriguez; Jairo Jhonatan Marquina Araujo; Jhonny Wilfredo Valverde Flores (Brazilian Archives of Biology and Technology)
Abstract The objective of this research was to evaluate how pressure, time, and type of gas in micro-nanobubbles affect the removal of heavy metals arsenic, antimony, and cadmium in acidic effluents. A three-factor experimental design was employed, varying the type of gas (air and oxygen), pressure (20, 40, and 60 psi), and treatment time (5, 10, and 15 minutes). To simulate the conditions of an acidic effluent, a solution with an initial pH of 1.77 was prepared in the laboratory, which, in contact with sulfide minerals containing iron, arsenic, antimony, and cadmium, was leached and subsequently adjusted to a pH of 6.5 by adding lime. The results showed significant variation in metal removal by adjusting the pressure and type of gas: with oxygen at 60 psi, arsenic removal reached 48.31%, while with air at 20 psi it reached 83.59%. For antimony, the highest removal with oxygen was 27.34% at 40 psi, compared to 90.78% with air at the same pressure. The exposure time to micro-nanobubbles (MNB) did not produce significant changes in metal removal. In conclusion, it is evident that pressure and type of gas are critical factors in the efficiency of heavy metal removal, more so than the duration of the treatment with micro-nanobubbles.